Real dependencies and significant correlations for the indicator “conformity ― non-conformity” (the model of quarts of independent variable) - M. M. Basimov (Вестник университета)
The article discusses the typology of significant connections for the indicator “Group-Oriented – Self-Reliant” (“ conformism – non-conformism”) (oriented at the group – independent) within the framework of studying statistical connections with the author’s method and correlation analysis. A total of 13 significant connections were identified, two of which are moderate (the maximum is 0.41), and the rest are very weak or weak in the range from 0.19 to 0.3. It means that in terms of linear mo dels they can be ignored. At the same time, among these 13 dependencies, two strong simplest nonlinear dependencies can be distinguished which are truly crucial for the research. The strong nonlinear dependency of the variable “ Ideosyncratic type” on the variable “Group-Oriented – Self-Reliant” (“conformism – non-conformism”) was considered in detail, as well as the connection of two significant dependencies of the variables “psychopathy” and “Hermit personality type” with the same variable for comparison. All the three dependencies are similar in their linear component and within the framework of the modern approach, popular among psychologists, should be treated as a meaningful result of the study. However, in reality, only one of them is interesting to the researcher. For visual representation, graphical comparisons of the three with each other and with their regression models built on the basis of linear correlation are considered. This indicates the non-linear nature of the dependencies of the indicator “Group-Oriented – Self-Reliant” (“ conformism – non-conformism”) in the conducted psychological study.